Sexing Viking Age horses from burial and non-burial sites in Iceland using ancient DNA - Nistelberger, Heidi; Pálsdóttir, Albína Hulda; Star, Bastiaan; Leifsson, Rúnar; Gondek, Agata; Orlando, Ludovic; Barrett, James; Hallsson, Jón Hallsteinn; Boessenkool, Sanne (Journal of Archaeological Science, 2019)
International audience